Expansion and Intensification of the North American Monsoon During the Pliocene. Issue 6 (10th November 2022) - Bhattacharya, Tripti; Feng, Ran; Tierney, Jessica E.; Rubbelke, Claire; Burls, Natalie; Knapp, Scott; Fu, Minmin
Abstract: Southwestern North America (SWNA), like many subtropical regions, is predicted to become drier in response to anthropogenic warming. However, during the Pliocene, when carbon dioxide was above pre‐industrial levels, multiple lines of evidence suggest that SWNA was much wetter. While existing explanations for a wet Pliocene invoke increases in winter rain, recent modeling studies hypothesize that summer rain may have also played an important role. Here, we present the first direct evidence for an intensified mid‐Pliocene monsoon in SWNA using leaf wax hydrogen isotopes. These new records provide evidence that the mid‐Pliocene featured an intensified and expanded North American Monsoon. Using proxies and isotope‐enabled model simulations, we show that monsoon intensification is linked to amplified warming on the southern California margin relative to the tropical Pacific. This mechanism has clear relevance for understanding present‐day monsoon variations, since we show that intervals of amplified subtropical warming on the California margin, as are seen during modern California margin heat waves, are associated with a stronger monsoon. Because marine heat waves are predicted to increase in frequency, the future may bring intervals of "Pliocene‐like" rainfall that co‐exist with intensifying megadrought in SWNA, with implications for ecosystems, human infrastructure, and water resources. Plain Language Summary: The middle Pliocene, an interval approximately 3 million years ago, has long puzzled climate scientists. Despite having higher‐than‐preindustrial carbon dioxide levels, which should result in drier conditions in subtropical regions, some subtropical regions were wet during the Pliocene. In southwestern North America, there were large permanent lakes and plant and animal species that cannot exist in arid regions. We used measurements of hydrogen isotopes in ancient plant matter to show that wet conditions in the Pliocene southwest resulted from a stronger monsoon. This stronger monsoon was caused by changes in subtropical and tropical ocean temperatures in the eastern Pacific. This study presents the first direct evidence that monsoon changes caused wet conditions in the middle Pliocene. It also has relevance for the present, since we find evidence that present‐day changes in subtropical ocean temperatures can amplify the monsoon, via a mechanism that strongly resembles what happened in the Pliocene. Our study suggests that further studies of the Pliocene can shed light on how future monsoon changes may influence wildfire, landscapes, and water resources across the southwest. Key Points: Leaf wax hydrogen isotopes preserved in ocean sediments reveal evidence of a stronger mid‐Pliocene monsoon in southwestern North America Isotope‐enabled simulations show that a stronger monsoon resulted from a diminished east Pacific subtropical‐tropical temperature gradient This mechanism is relevant to understanding present‐day monsoon variability in response to California margin marine heat waves